The management of university processes at the Faculty of Physical Culture "Nancy Uranga Romagoza" of Pinar del Río - Niurka Rodríguez Masías; Bárbara C. Roba Lazo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
In Higher Education Centers teaching, research and extension must be integrated to achieve solve societal problems, and thus conceive conscious and responsible citizens, imbued with a general culture, scientific and humanist on the basis of a model flexible prioritize inter and multidisciplinary relations, taking into account the above is that the present work focuses on the analysis of the evolution of each of these substantive processes within the Faculty of Physical Culture "Nancy Uranga Romagoza" Pinar from the river. Management of the educational process arises in the institution based on the methodological strategy for achieving the objectives proposed in each academic year training, taking into account the type of educational process according to the Bachelor in Physical Culture, the disciplines and subjects, then educational groups are responsible for each teacher to manage the process through its preparation (meeting, consulting, tutorials and independent study, depending on the type of course). As for management in scientific research it arises that has research groups of teachers and students of the race for subjects that are responsible for carrying out this activity in response to the research and territorial priorities, branches and national organized in scientific circles or student scientific societies. With the power extension allows the main actors in the process (teachers and students) are more consciously incorporate from promoting the culture of their profession. Finally the Faculty of Physical Culture of Pinar del Rio has become a center of training and upgrading of professionals in the field of sport in the country and contributed to raising the general culture of the same, its integrated as university processes conducive to the harmonious development and the search for solutions to the main problems of the municipality.